2020
DOI: 10.1016/j.ctro.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-enhanced MRI MOLLI T1 mapping during chemoradiotherapy in anal squamous cell carcinoma

Abstract: a b s t r a c tBackground and purpose: Oxygen-enhanced magnetic resonance imaging (MRI) and T1-mapping was used to explore its effectiveness as a prognostic imaging biomarker for chemoradiotherapy outcome in anal squamous cell carcinoma. Materials and methods: T2-weighted, T1 mapping, and oxygen-enhanced T1 maps were acquired before and after 8-10 fractions of chemoradiotherapy and examined whether the oxygen-enhanced MRI response relates to clinical outcome. Patient response to treatment was assessed 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Prior to this study, we and others have demonstrated that OE-MRI can induce signal changes in healthy tissues [16,34], can identify, quantify and map hypoxic sub-regions in mouse [17][18], rat [19], rabbit [35] and human [36][37][38][39] tumours, and can track response to therapy in patients with lung cancer [18]. While our previous work has focused on the value of OE-MRI combined with a perfusion sequence to exclude necrosis [17][18], most of the studies listed above from other groups tend to perform OE-MRI without this additional step.…”
Section: Discussionmentioning
confidence: 98%
“…Prior to this study, we and others have demonstrated that OE-MRI can induce signal changes in healthy tissues [16,34], can identify, quantify and map hypoxic sub-regions in mouse [17][18], rat [19], rabbit [35] and human [36][37][38][39] tumours, and can track response to therapy in patients with lung cancer [18]. While our previous work has focused on the value of OE-MRI combined with a perfusion sequence to exclude necrosis [17][18], most of the studies listed above from other groups tend to perform OE-MRI without this additional step.…”
Section: Discussionmentioning
confidence: 98%
“…Applying OE-MRI into a clinical trial workflow heightens the importance of two relevant factors: acquisition time and patient motion. Patient motion is especially detrimental if the original region of interest moves out of the imaging field-of-view, which has also occurred in previous OE-MRI studies using 2D rather than 3D imaging techniques [38] , [61] . In this current study, patient motion was a nontrivial concern: patient motion in the z-plane occurred in 7/12 patients, resulting in the MOLLI T1 map capturing a different section of the tumour, rendering it unusable for OE-MRI analysis.…”
Section: Discussionmentioning
confidence: 87%
“…Unfortunately, the T2* maps in this study were excluded due to artefacts, so it was not possible to discern the underlying source of this positive ΔR1 ox-air observed in the non-responder, however this demonstrates the importance of the inclusion of other measurements in the MRI protocol such as R2*. Therefore, although this study contained a small sample size (n = 5, other published OE-MRI clinical data has contained 4 [34] , 5 [13] , 6 [14] , 7 [37] , 7–9 [38] , 10 [17] , and 15 [18] subjects), the OE-MRI responses observed were consistent with the underlying OE-MRI theory and previously reported tumour OE-MRI responses.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations